Numerical Compensation of Air Absorption of Sound in Scale Model Measurements - ĆIRIĆ, Dejan G.; PANTIĆ, Aleksandar (Archives of Acoustics, 2012)
The absorption of sound in air represents one of the main problems of the scale model measurements.This absorption, especially at higher frequencies, is considerably greater than the value determined bythe law of acoustical similarity between the full scale and the scale model. Different alternatives areapplied for compensation of the excess air absorption including a numerical compensation. In this paper,a modified approach to numerical compensation is proposed. It is based on compensation of the sounddecay only, and not background noise. As a consequence, there is no an increase of background noise inthe compensated impulse response. The results obtained by the proposed procedure are compared to thecorresponding ones obtained by the other procedures.